HIV‐1 subtypes and drug resistance in children during antiretroviral therapy in Brazil. Issue 8 (8th April 2021) - de Andrade Arrais, Claudia R.; Lima, Kledoaldo; Barreiros, Marta; Rodrigues, Jessyca K. F.; Sousa, Nilviane P. S.; Costa, Daniel D.; Santos, Francisco D. R. P.; Pereira, Gerson F. M.; e Silva Viana, Antonia I.; Barros, Allan K.; Leal, Élcio
Abstract: We evaluate the genetic characterization of 132 HIV‐1 pol sequences from children and adolescents undergoing antiretroviral therapy in Northeast Brazil. Phylogenetic and recombination analyses were performed using the maximum likelihood method using SeaView version 4 and SIMPLOT software. Most individuals harbored HIV‐1 B (84.8%) and BF recombinants (9.8%), although other non‐B subtypes were detected: HIV‐1 C (1.5%), HIV‐1 F (2.4%), and BC recombinants (1.5%). Antiretroviral resistance was 47% (95% confidence interval [CI]: 38.7%–55.4%). Non‐nucleoside reverse transcriptase inhibitors (NNRTIs) showed higher frequencies of primary mutations, with 40.9% (95% CI: 32.9%–49.4%), followed by nucleoside reverse transcriptase inhibitors (NRTI) and protease inhibitors (PIs) with 34.8% (95% CI: 27.3–43.3) and 6.1% (95% CI: 3.1%–11.5%), respectively. Among NRTIs, higher resistance levels were observed for abacavir, emtricitabine, and lamivudine; for NNRTI, nevirapine and efavirenz. The most common primary mutations found were M184V (29.5%), K103N (25%), M41L (9.8%), T215Y (8.3%), and G190A (8.3%). Our findings highlight the importance of surveillance of resistance mutations, which contributes to the continuous updating and implementation of preventive measures to decrease mother‐to‐child‐transmission and transmitted drug resistance. Highlights: The predominance of HIV‐1 subtype B (84.8%) and BF recombinants (9.8%) in children (Brazil). Antiretroviral resistance was observed in 47% of children under virological failure. Nucleoside and Nonnucleoside Reverse transcriptase Inhibitors demonstrated higher drug resistance rates than protease inhibitors. NRTI and NNRTI‐resistants participants harboured resistance to three or more drugs in 91.3% and 79.6% patients, respectively. Most frequent Drug Resistance Mutations: NRTI (M184V, M41L, T215Y, D67N, K70R); NNRTI (K103N, G190A, K101E).